Numerical Modeling and Simulation of Tsunami Hazards in South Seram Island, Indonesia: A Case Study on Kairatu Fault - Teddy Dwi Riadi; Simon Tubalawony; Yunita Angnetije Noya; Verry Bambang Sakiran (Maritime Park: Journal of Maritime Technology and Society, 2026)
This study aims to analyze the potential for tsunamis caused by tectonic activity along the Kairatu Fault and to evaluate inundation patterns based on numerical modeling results using the COMCOT software. The Kairatu Fault is an active structure in the western part of Seram, with the potential to generate significant earthquakes and trigger tsunamis around Piru Bay and the waters of Ambon. Modeling was conducted using bathymetry data, earthquake source parameters, and seafloor deformation derived from the Okada model. Tsunami simulations were performed to estimate the maximum wave height, wave arrival time, and wave energy distribution along the coastline. Simulation results indicate that the southern coastal areas of Seram and the western coast of Ambon are highly vulnerable to inundation, with wave heights reaching 2–3 m and arrival times around 15–25 min after the earthquake event. Based on these modeling results, it is recommended that the early warning system and coastal spatial planning be strengthened to support tsunami disaster mitigation efforts in the area.